Sustainable use of longan seed waste as a natural coagulant aid for low-cost and eco-friendly water treatment - Anuwat Aunkham; Vivat Keawdounglek; Wei Chung Sim; Budsakorn Aiyee; Ploypairin Choochan; Phitchayapha Chumueang; Wichuda Intawong; Natcha Thambun; Anantaya Anantaburi; Panadda Klinchan (PLoS ONE, 2026)
Conventional water treatment relies on chemical coagulants like alum, which, despite being effective, generate harmful alumina residues and significant non-biodegradable sludge. Furthermore, alum is costly and associated with neurological risks and freshwater acidification. Seeking safer, eco-friendly, and cost-effective alternatives, this study systematically evaluated the coagulation efficiency of Longan Seed Powder (LSP), derived from the abundant agricultural waste of the Dimocarpus longan fruit. LSP, primarily composed of 82.31% starch, was characterized, and its potential was assessed in systematic Jar test experiments conducted in 1 L batches using kaolin-based synthetic and raw river water. To ensure statistical robustness, all conditions were performed in triplicate (n = 3), using both untreated (negative) and alum-only (positive) controls for comparison. When tested alone, LSP achieved limited turbidity removal (<25%). However, when used as a coagulant aid, 0.5 mg/L LSP combined with 1 mg/L alum (pH 4) demonstrated powerful synergistic effectiveness. The optimal system achieved a 96.7% turbidity reduction in synthetic water, performance comparable to using alum alone at a fivefold higher dose (5 mg/L) (96.5% removal). In raw river water (initial 50 NTU), this combination reduced turbidity by 85.0% while minimizing changes in pH and TDS. The study confirms that LSP, through its starch-based functional groups, contributes to coagulation primarily via charge neutralization and polymer bridging. With a low production cost of just THB 9.78/kg (USD 0.30/kg), LSP is demonstrated to be an effective and economically viable natural coagulant aid. These findings support decentralized, eco-friendly water treatment systems by valorizing agricultural waste and significantly reducing chemical usage. This research provides the first systematic evaluation of the LSP-alum combination in both synthetic and natural waters.